2003
DOI: 10.1016/s0168-6496(03)00106-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent changes in the soil bacterial community in limed and unlimed soil

Abstract: A humus soil with a pH(H(2)O) of 4.9 was limed to a pH of 7.5 and was incubated together with samples from unlimed and field limed (pH 6.1) soils at 5, 20 and 30 degrees C for up to 80 days. The changes in the phospholipid fatty acid (PLFA) pattern were most rapid for the bacterial community of the soil incubated at 30 degrees C, while no changes were found in the soil incubated at 5 degrees C. The response of the community activity to temperature was measured using the thymidine incorporation method on bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 35 publications
4
90
0
2
Order By: Relevance
“…maintenance of membrane fluidity or synthesis of cold-tolerant enzymes (Margesin et al 2007). Moreover, microbial community structure changes under contrasting temperatures regimes, favoring microbes better adapted to the new temperatures (Zogg et al 1997;Pettersson and Bååth 2003;Firestone 2004, 2006). Therefore it is possible that soil microbial community under cold conditions may have developed mechanisms of acclimation to these sub-optimal temperatures (cold-acclimation).…”
Section: Discussionmentioning
confidence: 99%
“…maintenance of membrane fluidity or synthesis of cold-tolerant enzymes (Margesin et al 2007). Moreover, microbial community structure changes under contrasting temperatures regimes, favoring microbes better adapted to the new temperatures (Zogg et al 1997;Pettersson and Bååth 2003;Firestone 2004, 2006). Therefore it is possible that soil microbial community under cold conditions may have developed mechanisms of acclimation to these sub-optimal temperatures (cold-acclimation).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies (Ranneklev and Bååth, 2001;Pettersson and Bååth, 2003;Hartley and Hopkins, 2008;Bárcenas-Moreno et al, 2009) have demonstrated that soil microbial communities can adapt to elevated temperature regimes. For example, using growth rate as a variable, Ranneklev and Bååth (2001) have shown that heating peat soil from 25-55 1C resulted in community adaptation with optimal growth at 55 1C in only 3 days.…”
Section: Discussionmentioning
confidence: 98%
“…About 30 , however, sampling was not conducted, since bacterial activity is so low as not to show any substantial changes in community structure during winter in cool-temperate regions (41,42) and soil is frozen during winter in TOEF. Soil samples were packed in plastic bags and kept in a cool icebox.…”
Section: Collection Of Soil Samplesmentioning
confidence: 99%